CHEILOSCOPY: A USEFUL ADJUNCT TO FORENSIC IDENTIFICATION- A STUDY OF 200 INDIVIDUALS (Journal of Forensic Medicine & Toxicology, 2012)
Establishing a person’s identity is the most challenging subject for researchers. With use of gloves, fingerprints are absent at the crime scene, lip prints recovered from objects can be traced and analyzed. Cheiloscopy is examination of furrows and grooves on the lips forming characteristic pattern. They are permanent and positive means of criminal identification and sex determination. This study done on 200 subjects, proved uniqueness of lip prints. The reticular and intersecting (52%) was the commonest pattern in males and full and partial length (70%) in females. 95% males and 96% females were identified correctly with an accuracy of 90.5%.
Keywords: Cheiloscopy; Sex determination; Criminal identification